Early Experience Implementing Long-Acting Injectable Cabotegravir/Rilpivirine for Human Immunodeficiency Virus-1 Treatment at a Ryan White-Funded Clinic in the US South. (2nd September 2022) - Collins, Lauren F; Corbin-Johnson, Della; Asrat, Meron; Morton, Zoey P; Dance, Kaylin; Condra, Alton; Jenkins, Kimberly; Todd-Turner, Marie; Sumitani, Jeri; Smith, Bradley L; Armstrong, Wendy S; Colasanti, Jonathan A
Abstract: Background: Long-acting injectable (LAI) antiretroviral therapy (ART) has the potential to improve medication adherence, reduce human immunodeficiency virus (HIV) stigma, and promote equity in care outcomes among people with HIV (PWH). We describe our early experience implementing LAI-cabotegravir/rilpivirine (CAB/RPV) for maintenance HIV-1 treatment. Methods: We launched a pilot LAI-ART program at a large Ryan White-funded clinic in the Southeast, which accept provider-initiated referrals from April 14, 2021 to December 1, 2021. Our interdisciplinary program team (Clinician-Pharmacy-Nursing) verified clinical eligibility and pursued medication access for eligible patients. We describe (1) demographic and clinical variables of PWH referred and enrolled and (2) early outcomes among those accessing LAI-CAB/RPV. Results: Among 58 referrals, characteristics were median age 39 (Q1–Q3, 30.25–50) years, 74% male, and 81% Black, and payor source distribution was 26% Private, 21% Medicare, 19% Medicaid, and 34% AIDS Drugs Assistance Program. Forty-five patients (78%) met clinical eligibility for LAI-CAB/RPV; ineligibility concerns included evidence of confirmed or possible RPV resistance ( n = 8), HIV nonsuppression ( n = 3), possible RPV hypersensitivity ( n = 1), and pregnancy ( n = 1). Among 45 eligible PWH, 39 (87%) enrolled and 15 (38%) initiated LAI-CAB/RPV after a median of 47 (Q1–Q3, 31–95) days since enrollment. Conclusions: Implementing LAI-ART at a Southern US Ryan White-funded clinic has been challenged by the following: substantial human resource capital to attain drug, administer injections, and support enrolled patients; delayed therapy initiation due to insurance denials; patient ineligibility primarily due to possible RPV resistance; and inability to provide drug regardless of payor source. These barriers may perpetuate disparities in ART access and outcomes among PWH and should be urgently addressed so that LAI-ART can be offered equitably. Abstract : Long-acting injectable antiretroviral therapy may improve adherence, reduce stigma, and promote equity in care outcomes among people with HIV. Implementing a pilot program in the US South was challenged by substantial human resource capital, insurance coverage barriers, and patient ineligibility.